2011
DOI: 10.1530/eje-11-0536
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting pegylated human GH in children with GH deficiency: a single-dose, dose-escalation trial investigating safety, tolerability, pharmacokinetics and pharmacodynamics

Abstract: Objective: GH replacement therapy currently requires daily injections, which may be inconvenient and distressing for young patients. This study determined the safety, tolerability, pharmacokinetics and pharmacodynamics of escalating single doses of a pegylated GH (NNC126-0083) developed for onceweekly administration, in children with GH deficiency (GHD). Design and methods: Thirty children (age R6 and %12 years, weight R16 kg) were randomised to NNC126-0083 or daily GH treatment. The subjects discontinued thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…NNC126-0083 was well tolerated, and no lipoatrophy was observed [37]. In 30 children with GHD randomized to a single dose of NNC126-0083 vs daily GH, a rise in IGF-I levels was observed in all NNC126-0083 dose groups; however, a satisfactory once-weekly IGF-I profile was not reached within the NNC126-0083 dose levels administered [38], and further development was stopped.…”
Section: Nnc126-0083mentioning
confidence: 98%
See 1 more Smart Citation
“…NNC126-0083 was well tolerated, and no lipoatrophy was observed [37]. In 30 children with GHD randomized to a single dose of NNC126-0083 vs daily GH, a rise in IGF-I levels was observed in all NNC126-0083 dose groups; however, a satisfactory once-weekly IGF-I profile was not reached within the NNC126-0083 dose levels administered [38], and further development was stopped.…”
Section: Nnc126-0083mentioning
confidence: 98%
“…No lipoatrophy was noted and there were no neutralizing antibodies. In a 6 month phase 2 study of 43 young adults with childhood onset GHD ARX201 was shown to be well-tolerated and improved body composition, lipid profile and quality of life [38]. A dose dependent increase in IGF-I was observed [39].…”
Section: Arx201mentioning
confidence: 99%
“…Conjugation of GH to albumin decreased renal clearance and increased half-life; however, this formulation did not exhibit an improved bioavailability in comparison to rhGH 6 . PEGylated GH demonstrated local injection site lipoatrophy in adults and children, thus raising a safety concern 7 ; an additional study with PEGylated GH demonstrated an inadequate IGF-1 response 8 . Another approach involved the fusion of an unstructured amino acid sequence (XTEN) to hGH in order to reduce its renal clearance (VRS-317) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…37 De Schepper et al developed another PEGylated rhGH called NNC126-0083 to attain a onceweekly preparation. 37 Lipoatrophy was not observed in 30 children, but further research was required to ensure its safety by testing it in adults and more subjects. However, the IGF-1 profile was not satisfactory, since the response began subsiding 3 days after injection, rather than lasting for 1 week as planned.…”
Section: Extending Half-life Of Hghmentioning
confidence: 99%